Two-year impact of the Spanish smoking law on exposure to secondhand smoke: evidence of the failure of the 'Spanish model'. Issue 4 (9th June 2011) - López, Maria J; Nebot, Manel; Schiaffino, Anna; Pérez-Ríos, Mónica; Fu, Marcela; Ariza, Carles; Muñoz, Gloria; Fernández, Esteve
Abstract : Objective: Studies evaluating the long-term impact of smoking laws on secondhand smoke (SHS) exposure using airborne markers are scarce. This study aimed to assess the long-term impact of the Spanish smoking law on SHS levels, using a specific and objective marker. Methods: Follow-up study, measuring vapour-phase nicotine levels before the implementation of the law and 6, 12 and 24 months after the initial assessment. A total of 443 samples were taken at baseline in eight different regions in offices in the public administration, private sector, universities and hospitality venues. Results: Two years after the law was implemented, the nicotine concentration decreased by a minimum of 60% in public administration, university and private sector offices, as well as in venues where smoking was totally banned. However, nicotine levels significantly increased by 40% in hospitality venues allowing smoking. No significant differences were found in hospitality venues with areas for smokers and non-smokers or in pubs and discotheques. Conclusions: Two years after the smoking law came into force, levels of SHS exposure in the workplace were significantly lower than before the law was implemented. Importantly, however, SHS levels were even higher than before the law was implemented in venues still allowing smoking. The data obtained in this study clearly show that the 'Spanish model' is not protecting the health of hospitality workers and that a complete ban is required. Furthermore, this study highlights the importance of long-term monitoring of compliance with smoking laws over time.